Onset of ratchetting in pressurised fibre glass reinforced epoxy (FRGE) piping subjected to cyclic axial strain - Khairul Salleh, Basaruddin (Universiti Sains Malaysia (USM), 2011)
Organized by Universiti Sains Malaysia, 1st - 3rd June 2009 at Bayview Beach Resort, Batu Ferringhi, Penang, Malaysia.